Scooby-Doo! World of Mystery 40 Brazil - Sugar Loaf Mountain - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang face a creepy voodoo doll who is trying to stop the all important carnival samba contest!
Keywords: Juvenile literature-Fiction